2007
DOI: 10.1017/s1355617707071329
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of alexithymia in Parkinson's disease

Abstract: There are recent reports that alexithymia may be associated with brain dysfunction involving frontal lobes or right hemisphere regions. However, little is known about the relationship between alexithymia and cognitive deficits in Parkinson's disease (PD). The authors investigated the neuropsychological correlates of alexithymia in a population of 70 nondemented PD patients and 70 controls. Alexithymia was screened using the 20-item version of the Toronto Alexithymia Scale (TAS-20). Standardized scales that mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Neuropsychological scale-based studies have demonstrated a high incidence of somatization and alexithymia in PD, reaching a prevalence of 40%,89,102 whereas in our cohort study of somatoform disorders, the effort to classify, confidently, different motor, and nonmotor symptoms, as functional, and specifically differentiating them from motor and nonmotor symptoms in PD, resulted in a much lower incidence in PD of 7%–9% and 15%–19% in DLB 85…”
Section: Methodsmentioning
confidence: 56%
“…Neuropsychological scale-based studies have demonstrated a high incidence of somatization and alexithymia in PD, reaching a prevalence of 40%,89,102 whereas in our cohort study of somatoform disorders, the effort to classify, confidently, different motor, and nonmotor symptoms, as functional, and specifically differentiating them from motor and nonmotor symptoms in PD, resulted in a much lower incidence in PD of 7%–9% and 15%–19% in DLB 85…”
Section: Methodsmentioning
confidence: 56%
“…Using the above mentioned keywords, forty one studies were listed, out of which thirteen did not fulfil the inclusion criteria: eleven did not measure alexithymia or did not provide information about how alexithymia was associated with performance and/or brain activity [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], and two used the Schalling-Sifnéos Personality Scale to measure alexithymia [48], [49], the validity of which has been questioned [20]. Finally, four studies measured behaviours other than the decoding of EFEs [50], [51], [52], [53].…”
Section: Resultsmentioning
confidence: 99%
“…Alexithymia is an alteration in affect regulation (including the inability to identify and describe feelings, difficulty distinguishing feelings from bodily sensations of emotional arousal, impaired symbolization and an externally oriented cognitive style, usually associated to depression [63]. Only one study assessed the relationship between alexithymia and cognitive functions in PD patients [64]: alexithymic PD patients had worse performances relative to non alexithymic PD patients in tasks requiring visuospatial processing, suggesting that the right hemisphere is involved in the development of alexithymic features.…”
Section: Other Affective Disordersmentioning
confidence: 99%